Effectiveness of passion branding in the GSM sector of Turkey and the consumers’ valuation of GSM operators as passion branders - Eker, Tutku (My University, 2004)
Başarılı bir pazarlamacı olmanın temel yolu tüketicilerin isteklerini sürekli takip etmek ve bu doğrultuda beklentilerini karşılayacak ürün ve servisler sunmaktan geçer. Günümüz tüketicileri artık ürünlerin sadece fiziksel özelliklerinden tatmin olmamakta, o ürüne bağlanabilecekleri duygusal değerleri de göz önünde tutmaktadırlar. Bu sebeple, bu araştırma pazarlamanın değer katma boyutlarından biri olan tutkusal markalama üzerine odaklanmıştır. Bu yeni strateji, basit şekliyle tüketicilerin tutkuyla bağlı oldukları alanlarla markayı özdeşleştirmeyi hedeflemektedir. Bu vesileyle, tüketicilerin kendileri için bir anlam teşkil eden markayı seçmeleri beklenmekte ve nihai olarak, satışların ve marka değerinin artması ve şirketin rakiplerden farklı bir konuma oturması ümit edilmektedir. Bu konuyla ilgili ampirik araştırma yetersizliğinden ötürü, bu çalışma Türkiye'deki GSM sektöründe tutkusal markalamanın fayda getirip getirmeyeceğini araştırmayı amaçlamış ve tüketicelerin üç GSM operatörünü (Turkcell, Telsim ve Aria/ Aycell) bu stratejiyi uygulama yeterliliklerine gore değerlendirmelerini sağlamıştır. Fakat, elde edilen bulgular tüketicilerin bakış açısıyla değerlendirilen üç GSM şirketin tutkusal markalama stratejisini uygulamadıklarını göstermştir. Bu sebepledirki, şirketlerin yapmış oldukları çeşitli destekleme kampanyaları beklenen faydaları sağlamamaktadır.

In order to be a successful marketer it is very important to track what consumers expect from goods and services. Today's consumers are no longer satisfied with the tangible attributes or benefits of the products, but there are other certain issues they consider. When they simply purchase an item, consumers also give importance to its emotional value, something they really care about other than the product itself. Therefore, this study will concentrate on one of the adding value dimensions of marketing, namely passion branding. This new strategy simply suggests identifying the brand with the issues that consumers are passionate about. Through this way, it is expected that consumers will choose the brand, since it stands for something, and thus, sales will rise, brand equity will enhance, and the company will differentiate itself from the competitors. Also, the commitment of the employees and stockholders to the company is thought to increase. Because of the scarcity of empirical research on this area, this study aimed to see whether passion branding works in the GSM sector of Turkey, which also provided insights as to whether consumers see any one of the GSM operators as passion branders. However, as the findings revealed, consumers do not entitle any of the GSM operators as passion branders. Therefore, the supportive campaigns undertaken by these companies do not seem to bring the benefits as much as passion branding does.
Keywords: Genel yönetim; Pazarlama; Pazarlama yönetimi